Microsoft Exchange Server 2000 - Redmond, Tony (Tecniche nuove, 2001)
Documents practices and techniques that have been developed for managing the Exchange messaging application<-->mainly with an eye on large deployments<-->and for upgrading from version 5.5 to Exchange 2000. The author, who is vice president at Compaq Global Services, discusses the web storage system, storage groups, instant messaging, and the interaction between Exchange 2000 and the Windows 2000 active directory